Emergence and evolution of virtual classrooms, and e-learning tools - Soriano Hernández, Jennifer Vanessa; Solís Sánchez, Ana Elizabeth (2024)
The following report shows a summary of the specialization course in which the material and activities seen during the three modules that comprise the course are exposed. Each module contains material oriented to teaching English with virtual tools that facilitate this new teaching modality and techniques that have been adapted for it. The activities and material are broken down by module, as each one is oriented with different educational purposes to best cover virtual teachings, such as theories, tools, and techniques. Likewise, as students we will make a summary of what we have learned during the three modules, detailing the activities carried out to put into practice the information provided by the teachers. We will also show part of the activities and didactic material created to fulfill the tasks assigned to this course. Key Words: Virtual tools ; New teaching modality ; Teaching techniques ; Didactic material ; Learning management system.